The New Speaking Progress Test Design for Economics and Business Students in Indonesia - Adhi Kusuma; Warissara Audjam (Universitas Sarjanawiyata Tamansiswa, 2019)
This study is to see the application of a new designed speaking progress test for the English 4 subject which has not done yet at one of the university in Indonesia. This aims to assess students during their learning and needs, and to evaluate the course. The new speaking test design was a progress test run formally on semester 4. It was adopted the model of IELTS test which consisted of three parts, used the TSE scoring scale and ETS rater system. All aspects in this test follow the compulsory requirements of a test such as reliability, validity, practicality, and impact. The test was a face-to-face interview test (Weir, 2005, p. 143). Time allocated for the entire test was not more than 15 minutes. The data taken from the five chosen trial students of semester 5. The actual test design was intended for the student of semester 4, but the examiner and the rater were the real ones. However, the age, learning background, and the general proficiency level of these five trial students were nearly similar to the intended candidates for the test design. Since the TSE was not familiar to the students, the students got two kinds of score. The first final result of the TSE score were between 40–50. The second final result was scored using the range of 100. It showed between 66.7–83.3. Both of the final results showed that this new design really tested the progress of the students. The design met the students’ needs and evaluates the course. This innovative model of test was proposed to be trialled in the progress test in semester 4 next year.Keywords: Speaking Test, IELTS model